The Farabi conceptualisation of "social health" and global moderation - Faramarzgharamaleki, Ahad (HTS teologiese studies, 2018)
Globalisation today has collapsed cultural and social boundaries and has turned humanity into a global family. Its result is humanity’s common fates and its new threats, as extremism. Here, extremism is analysed within the framework of health approach, in the broader sense of the term. This analysis is based on the political philosophy of Abā Naṣr Farabi (873–950 AD), the founder of Islamic philosophy. He applies the concept of health to the civil (polis) with two definitions: (1) moderate and (2) virtuous structures. There is a casual connection between these two definitions: deration as the source of health and extremism as the source of disease. Maintaining the moderation of society requires an ethical assessment of the laws and policies. Lack of ethical ground in many theories and policies of development are the main cause of extremism. In its various forms, exclusivism is another important cause of extremist mentality. Media can prevent and heal extremism in different ways, especially by re-imagining common destructive images.